Neopatrimonialism and agricultural protection: The case of maize in Malawi - Phiri, Horace; Edriss, Abdi Khalil (International Food Policy Research Institute, 2013)
This empirical study uses data from 1970 to 2010 to estimate levels of neopatrimonialism in Malawi. We then test how neopatrimonialism has affected policy-induced agriculture producer incentives. Three dimensions are used to measure neopatrimonialism – systematic clientelism, a power concentration index, and control of corruption. All were negatively related to the level of producer support provided farmers by government. This suggests that the manifestation of a patronage system creates policy-induced disincentives to agricultural production due to worsening corruption, concentration of political power, and a crowding out of development expenditure by the costs of maintaining a bloated civil service. This result reaffirms the belief that neopatrimonialism results in poor performance of the agricultural sector of countries in sub-Saharan Africa